2011
DOI: 10.1016/j.ejvs.2010.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Safety of Aorfix™ Stent Graft in Highly Angulated Necks – A Prospective Observational Study (Arbiter 2)

Abstract: The results of this study support the continued application of the Aorfix™ graft to the highly angulated neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 20 publications
(24 reference statements)
1
23
0
Order By: Relevance
“…Interestingly, the incidence of loss of proximal sealing length has been reported to be higher (6.7%) with the Aorfix stent graft. 20 The higher incidence of type I endoleak in our cohort might be explained by the severe proximal neck angulation (all patients with type I endoleak had severely angulated infrarenal neck, 84°/82°/73°) since no loss of distance from renal to graft was observed. Notably, the incidence of type Ia endoleak was 33% (2/6) in the subgroup of patients with Ͼ80°proximal neck angulation.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Interestingly, the incidence of loss of proximal sealing length has been reported to be higher (6.7%) with the Aorfix stent graft. 20 The higher incidence of type I endoleak in our cohort might be explained by the severe proximal neck angulation (all patients with type I endoleak had severely angulated infrarenal neck, 84°/82°/73°) since no loss of distance from renal to graft was observed. Notably, the incidence of type Ia endoleak was 33% (2/6) in the subgroup of patients with Ͼ80°proximal neck angulation.…”
Section: Discussionmentioning
confidence: 88%
“…A recent report evaluating 30 patients with angulated anatomies (all with neck angle Ͼ60°, including 63% with neck angle Ͼ75°) treated with the Aorfix stent graft, achieved lower clinical success (92.6%) within the first 6 months after the operation, with two recurrent type Ia endoleaks being reported. 20 Moderate (40%-59%) to severe (Ͼ60%) angulation of the proximal aneurysm neck has been demonstrated to be associated with acute or late adverse events following EVAR despite an adequate proximal aortic length (Ͼ20 mm) and, probably, regardless of the type of the endograft used. 14 Furthermore, previous reports have shown that endovascular treatment of aneurysms with an angulated neck Ͼ60°is commonly associated with adjunctive procedures, such as giant Palmaz (Cordis, Miami Lakes, Fla) stent or cuff placement to achieve proximal seal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations